Sistem Informasi Manajemen Program Keluarga Harapan Pada Dinas Sosial Kabupaten Tangerang - Abas Sunarya; Ely Nuryani; Mochamad Yusuf Romdoni (UNIVERSITAS RAHARJA, 2015)
Community service is very important to do as well as services provided to civil servants/private to public, in any place where companies and government agencies can be divided into several sub-sections to fit the field and their respective functions in the work. Similarly the social services at Serang District which has been divided into several sections, one of which is a sub section Hope Family Program in terms of helping very poor families who have previously registered as participants to this program. This program is a program that provides cash assistance to extremely poor families if they meet the requirements associated with efforts to improve the quality of human resources, education and health. The main objective of this program is helping to reduce poverty by improving the quality of human resources in extreme poverty. In practice, this is managed by Family Hope Program Implementation Unit in each district, In this case I find the problems or constraints that exist within Family Hope Program the classification of very poor families are less clear, the lack of updating an increase in the economic status of participants, and the absence of recapitulation of education facilities and health insurance in their respective districts in Serang District.